Physiological parameters of paraplegic skiing athletes in laboratory and field measurements - Goll, M.; Wiedemann, M. S. F.; Spitzenpfeil, P. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Physiological parameters of skiing athletes are well described in literature (e.g. Turnbull et al. 2010). Similarly, performance capacities of disabled athletes are also well-documented (e.g. Shephard 1988). Nevertheless, there is no information about these parameters in paraplegic skiing athletes. The purpose of the present study was therefore a thorough analysis of both laboratory and field measurements in paraplegic skiing athletes of German Paralympic National Team.